The physical, emotional, social, and functional dimensions of epidermolysis bullosa. An interview study on burdens and helpful aspects from a patients’ perspective - Gudrun Salamon; Sophie Strobl; Marie-Stephanie Matschnig; Anja Diem (Orphanet Journal of Rare Diseases)
Abstract Background Epidermolysis bullosa (EB) is a serious, painful, hereditary and still incurable genetic condition. Due to blistering or wounds on the skin caused by the slightest touch, a person suffering from epidermolysis bullosa is prevented from achieving the same quality of life as a healthy person. Until now, psychosocial research has focused on the description of the problems of people living with the disease. Objectives The aim of this paper is to provide a structured overview of potential psychosocial effects of epidermolysis bullosa on the everyday lives of people with the condition and to explore helpful aspects for coping with EB. Methods Semi-structured interviews with persons living with EB were conducted. Analyses were based on a combination of a reflexive grounded theory approach and a structured coding guide. By means of purposive sampling across three countries, a high diversity within the sample was achieved in order to obtain a wide range of possible effects. Results A total of 17 individuals living with EB across all EB types were interviewed, resulting in 36,315 words being analysed. Psychosocial aspects of EB comprise physical, emotional, social, and functional dimensions. Identified burdens and helpful aspects in dealing with EB are described along this structure. Conclusions Our results highlight the broad range of possible psychosocial effects caused by epidermolysis bullosa. It is particularly important to recognise those affected as individuals with their personal needs and to avoid unnecessary strains. Furthermore, emotional support is crucial in every respect.